Effect of dietary synbiotic supplementation on performance parameters in turkey poults administered a mixed Eimeria species inoculation I - Duff, Audrey F. (Poult Sci, 2020)
This study examined the effects a synbiotic feed additive (PoultryStar me(US)) on performance and intestinal health parameters in turkey poults administered a mixed Eimeria inoculation. The synbiotic feed additive consisted of Lactobacillus reuteri, Enterococcus faecium, Bifidobacterium animalis, Pediococcus acidilactici and a fructo-oligosaccharide prebiotic. Dietary treatments began on day of hatch, and poults were placed on a normal starter, starter containing Clinacox, or starter containing PoultryStar until the conclusion of the experiment on day 42. In addition, on day of hatch, all poults, with exception of the negative control, were orally inoculated with Salmonella enterica Enteritidis. On day 16, poults in inoculated treatment groups received an oral dose of Eimeria adenoides and Eimeria meleagrimitis oocysts resulting in a 2 × 3 factorial arrangement of treatments. BW were measured at weekly intervals after challenge, and fecal samples were collected from all pens during day 21 to day 33 to monitor fecal shedding and calculate oocyst per gram of feces. Five day after Eimeria inoculation, inoculated PoultryStar-fed (I-PS) and inoculated Clinacox-fed (I-CL) poults, on average, weighed and gained significantly more weight (P < 0.05) than inoculated controls (I-CON) and were similar to uninoculated treatments. Between day 21 and day 28, I-PS and I-CL poults showed a 23% improvement (P < 0.001) in percent change in BW gained relative to I-CON, and overall weight gain as a percentage was similar to the uninoculated control. Overall incidence of macroscopic intestinal lesions on day 21 and day 28 was low, but I-PS and I-CL poults were generally less positive than I-CON, and no oocysts were detected in the feces of any group except I-CON which cycled as expected. From this study, it can be concluded that incorporating PoultryStar into the diet of poults reared to 6 wk ameliorates and prevents aspects of performance loss and negative impacts on gut health seen with mixed Eimeria inoculation.